Fungal contamination in a University building - Zoni, Roberta; Capobianco, Emanuela; Viani, Isabella; Colucci, Maria Eugenia; Mezzetta, Sandra; Affanni, Paola; Veronesi, Licia; Di Fonzo, Davide; Albertini, Roberto; Pasquarella, Cesira (Acta Biomedica Atenei Parmensis, 2020)
Background. It is recognized that airborne fungi can cause illnesses in humans but data on environmental exposure are still poor. The aim of this study was to evaluate the fungal airborne contamination in a university building. Methods. The study was performed in February and May 2018; air samples were collected, before activity (on Monday) and during activity, (on Friday), both through active (CFU/m3) and passive (Index of microbial air contamination, IMA) method. Fungi were identified by using the scotch test. Results. In February the median fungal contamination value decreased from 14 CFU/m3 before activity to 7 CFU/m3 during activity, while IMA median remains 0. Instead in May both increased during activity (from 87 to 140 CFU/m3; from 5.5 to 7.5 IMA). Overall values increased in May compared to February. Aspergillus spp., Penicillium spp., Cladosporium spp. Absidia spp. were the genera most frequently isolated in both months, while in May Chaetomium spp. e Ulocladium spp. were recovered too. Conclusions. Seasonal trend in the levels of fungal contamination of the air was observed, with a statistically significant increase in May. This study represents the first step of a wider study aimed at enhancing knowledge about air fungal contamination.